MORPHOPHONEMIC RULE OF PROCESS VERBS IN THE NOVEL DI BAWAH BAYANG-BAYANG ODE BY SUMIMAN UDU - S. Sarmadan; H. Hasniati (Universitas Sembilanbelas November Kolaka, 2017)
The purpose of this study was to describe the morphophonemic rules of inner process verbs Novel Di Bawah Bayang-Bayang Ode by Sumiman Udu. Spoken morphophonemic rules of sound changes or phonemic changes as a result of morphological processes (affixation processes, reduplication processes, and composition processes). The results showed that the morphophonemic rules in the novel Novel Di Bawah Bayang-Bayang Ode by Sumiman Udu namely (1) the morphophonemic rule of affix meN, (2) the morphophonemic rule of affix peN, (3) the affixed morphophonemic rule ber-, (4) the morphophonemic rule of the affix per-, and (5) the morphophonemic rule of affix ter-. There are five changes in affixed form in the Novel Di Bawah Bayang-Bayang Ode by Sumiman Udu, namely: (1) men-, (2) me-, (3) mem-, (4) meng-, (5) meny-. Changes in affixed forms peN in the novel Novel Di Bawah Bayang-Bayang Ode by Sumiman Udu were two, namely (1) pe- and (2) peny-. Affixes per-, ber-, and ter- that was in the Novel Di Bawah Bayang-Bayang Ode by Sumiman Udu was not experiencing a change in the form.